Día 1: El Triásico de los alrededores de Nuévalos (Zona del Monastetrio de Piedra, Cordillera Ibérica). - Arche, A.; Rincón, R.; Vilas, Lorenzo; García Quintana, Álvaro; Garrido-megías, A.; Hernando Costa, S. (Cuadernos de Geología Ibérica, 1977)
Sin resumen